Peningkatan Hasil Belajar pada Konsep Penjumlahan Bilangan Bulat dengan Menggunakan Media Tabel Penjumlahan pada Siswa Kelas I SD Gmit 034 Wolwal - Desi Natalia Auw; Eunike Molebila; Jeni Marianti Loban (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
This community service research has a very important aim, namely to improve the ability to understand the concept of adding whole numbers in elementary school students through the use of addition tables in mathematics learning. This method can be an effective step in improving understanding of complex mathematical concepts at the basic level. Basically, mathematics is a subject that requires a strong understanding of concepts from an early age, especially in whole numbers. This service uses the addition table method which utilizes drawing an addition table on the blackboard. With this car, students can see directly how the process of adding integers is carried out in a more structured form. The research location at SD GMIT 034 Wolwal with subjects totaling 21 class I students, shows that this activity was carried out involving all students in that class. This provides a more accurate picture of the effectiveness of the tabular addition method in improving students' understanding of the concept of adding whole numbers. This method follows 6 well-designed stages, which help students understand the concept of addition in a step-by-step manner. The results show that a personal approach through addition tables provides significant benefits in mathematics learning, especially at the elementary level. The use of media such as addition tables can motivate students to learn mathematics better and understand concepts in more depth, strongly preparing them to understand more complex mathematical concepts in the future.